ON THE FUTURE OF THE BLUE ECONOMY: COMPARING INDONESIA’S ROLE IN THE ASEAN AND LAC REGIONS - Mulyaman, Darynaufal; Waluyo, Bambang Dwi; Maharani, Dewi Aulia (UI Scholars Hub, 2026)
This study aims to determine the concrete development and implementation of blue economy programs in the future by examining Indonesia's role in the context of international political economy, particularly through maritime diplomacy and cross-regional cooperation such as ASEAN, the Indonesia-Latin America and Caribbean Business Forum INA-LAC, and the Alliance of Island States AIS. Using a constructivist approach, this study concludes that Indonesia, as a middle-power country, utilises soft resources, such as maritime identity, sustainability values, and diplomatic leadership, to strengthen its position in global blue economy governance. The results of the study show that Indonesia has strategic potential for developing and implementing blue economy programs through a combination of diplomatic instruments, international cooperation initiatives, and normative leadership. This role not only strengthens Indonesia's position in global forums such as the 2023 ASEAN Power and the AIS Forum, but also provides advantages in international political economy, particularly in building legitimacy and support from other countries for Indonesia's national interests.